Penerapan Model Collaborative Learning Untuk Mengoptimalkan Kemampuan Berpikir Kreatif Peserta Didik Pada Pembelajaran Matematika - Julyana, Putri; Anggraini, Villia; Fitri, Dewi Yuliana (Imajiner: Jurnal Matematika dan Pendidikan Matematika, 2025)
This research stems from the fact that mathematics learning in schools still largely uses a teacher-centered expository approach. This condition causes students to lack a deep understanding of concepts and are unable to optimally demonstrate creative thinking skills. They tend to memorize formulas, have difficulty solving non-routine problems, are passive in discussions, and are not accustomed to expressing opinions. To address these issues, this study applies the Collaborative Learning (CL) model, which is oriented towards heterogeneous group cooperation to encourage active interaction, exchange of ideas, and collaboration in solving mathematical problems. This study aims to examine the effect of the application of Collaborative Learning on mathematical creative thinking skills compared to conventional learning. The approach used was an experiment with a Posttest Only Control Group Design. Samples were taken randomly and divided into experimental and control classes. The research instrument was a mathematical creative thinking ability test analyzed through the Liliefors normality test, F homogeneity, and t-test. The results showed an average posttest score of 64.67 for the experimental class and 62.50 for the control class, with a t-value of 0.305 and t-table of 1.68. Since t count t table, it was concluded that there was no significant difference between the two groups. This finding indicates that the implementation of Collaborative Learning has not shown a significant impact on improving students' mathematical creative thinking skills.